1990
DOI: 10.21273/jashs.115.5.775
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Ethanol Buildup and Off-flavor in `Murcott' Tangerine Fruits

Abstract: Britex and Zivdar, water-based polyethylene waxes, were applied in commercial and experimental formulations as spray coating, a single dip, or double dips on `Murcott' tangerine (Citrus reticulate Blanco) fruits. Postharvest waxing of `Murcott' tangerine reduced weight loss but affected the sensory characteristics of the fruit. Charges in fruit weight loss and juice composition occurred in the waxed fruits after 4 weeks of storage at 5C plus 1 week of simulated retail handlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(63 citation statements)
references
References 4 publications
8
52
0
3
Order By: Relevance
“…Both ethanol and ethyl acetate emit ethanol‐like, pungent, fruity and solvent odours, which contribute to the observed increases in sensations of ‘overripe’ and ‘off‐flavour’ odours (Table ). Indeed, build‐up of ethanol and ethyl acetate levels during postharvest storage was previously related to accumulation of off‐flavours in other fruit also (Cohen et al ., ; Shi et al ., ). Furthermore, we found that ethanol levels accumulated during pronged storage to high levels much above its reported odour threshold (Table ), and therefore, it probably indeed affected fruit flavour perception.…”
Section: Discussionmentioning
confidence: 99%
“…Both ethanol and ethyl acetate emit ethanol‐like, pungent, fruity and solvent odours, which contribute to the observed increases in sensations of ‘overripe’ and ‘off‐flavour’ odours (Table ). Indeed, build‐up of ethanol and ethyl acetate levels during postharvest storage was previously related to accumulation of off‐flavours in other fruit also (Cohen et al ., ; Shi et al ., ). Furthermore, we found that ethanol levels accumulated during pronged storage to high levels much above its reported odour threshold (Table ), and therefore, it probably indeed affected fruit flavour perception.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively low concentrations of ethanol and acetaldehyde have been proven to enhance the taste and flavour of fresh fruit (Paz, Ianes, Prevost, & Frenkel, 1981). By contrast, high accumulation of these volatiles in the juice may contribute to causing of off-flavour and bad taste (Cohen, Shalom, & Rosemberg, 1990;Shaw, Wilson, & Berry, 1981), although components other than ethanol may accumulate in fruit and adversely affect the organoleptic traits of citrus fruit (Baldwin, NisperosCarriedo, Shaw, & Burns, 1995;Moshonas & Shaw, 1997;Pesis & Avissar, 1989). In our study we found notable post-heat increases in ethanol in 'Olinda' and 'Campbell' juice and the deterioration of the oranges' organoleptic characteristics.…”
Section: Article In Pressmentioning
confidence: 99%
“…Despite their attractive appearance and convenience for consumption, mandarins are much more perishable than other citrus varieties and suffer from much shorter postharvest storage lives of just a few weeks 2, 3. One of the major problems in maintaining the quality of mandarin fruits after harvest is their rapid deterioration in flavour and sensory acceptability, mainly due to accumulation of off‐flavour volatiles 2, 4…”
Section: Introductionmentioning
confidence: 99%